An Estimate of a Structural Hedonic Price Model of the Housing Market: An Application of Rosen's Theory of Implicit Markets - Witte, Ann D.; Sumka, Howard J.; Erekson, Homer (Econometrica, 1979)
Ann D. Witte, Howard J. Sumka, Homer Erekson, An Estimate of a Structural Hedonic Price Model of the Housing Market: An Application of Rosen's Theory of Implicit Markets, Econometrica, Vol. 47, No. 5 (Sep., 1979), pp. 1151-1173